Jesus as a Historical Man Based on Oddbjørn Leirvik’s Thoughts: Interreligious Dialogue between Islam and Catholicism - Yuniarto, Petrus; Kwirinus, Dismas (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
This article discusses Jesus anthropologically and his implication as well as historicity in the Islamic context. In Islam, Jesus is called ‘Īsā al-Masīḥ. In this article we discuss Jesus in the Quran and the Hadith, the anthropology of Jesus in Islam, the miracle of Jesus in the Islamic context, the Christian polemic against Islam in the Middle Ages and the dialogue and peace between Christians and Muslims. The method employed is content analysis of relevant primary and secondary data. The data collection method uses library research to explore various reference sources. The primary and secondary data obtained are then analyzed using a qualitative approach. The result is that the figure of Jesus based on Oddbjørn Leirvik’s thought can be used to promote harmony and peace in religious relationships, and it is very relevant to Indonesian context. The awareness of the figure of Jesus based on Islamic and Catholic teachings is essential to promote harmony especially in Indonesia.